Agro-Ecological Assessment of Forage and Fodder Species Diversity in Nepal - Rai, Sajana (Agronomy Journal of Nepal, 2025)
Livestock production suffers from a seasonal feed imbalance, with an abundance of green forage during the monsoon and a scarcity in the spring and winter in Nepal. Utilizing a wide range of fodder crops is essential to overcoming this obstacle. Approximately 275 cultivated plant species have been identified as forage species in Nepal, out of the approximately 510 forage species that are readily available. Furthermore, Nepal has more than 500 species of fodder trees. Approximately 250 tree species are regarded as economically important fodder trees among them. Due to their greater biomass, palatability, and adaptability, farmers in the Terai and mid-hill regions grow both native and introduced grass species, such as fodder oats (Avena sativa) and Napier grass (Pennisetum purpureum). Certain pasture grasses, like timothy, Setaria, and ryegrass (Lolium spp.), are planted in higher, colder climates. Because of their increased protein content and ability to fix nitrogen biologically, leguminous forages such as vetch, joint vetch, and forage peanut are being encouraged more and more. Certain fodder tree and shrub species, such as Premna integrifolia (Ginderi), Ficus semicordata (Khanayu or Nebharo), and Artocarpus lakoocha (Khanyu), are thought to be essential to traditional cattle farming and agroforestry systems. The diversity, distribution pattern, and seasonal availability of Nepalese forage and fodder species are examined in this review paper, with an emphasis on their potential for genetic improvement. Utilizing diverse fodder and forage species guarantees year-round feed availability in Nepal’s various agro-ecological zones.